An exploration of the relationship between herbal medicine use and anti-retro viral therapy adherence among people living with HIV in Blantyre, Malawi. - Noniwa, Thokozani (2021)
Antiretroviral Therapy(ART) adherence is defined as being able to consistently take 95% of the prescribed Antiretroviral(ARV) drugs by an HIV infected person. According to the World Health Organisation(WHO), most people living with HIV and AIDS in Africa use also herbal medicines to treat opportunistic infections and obtain symptomatic relief. The main objective of this research was to explore potential relationship between use of herbal medicine and Antiretroviral Therapy adherence among People Living with HIV. Specifically, the study was designed to determine use of herbal medicine among People Living with HIV, establish patterns of herbal medicine use, explore potential interruption to ART medication due to herbal medicine use and determine associated factors for herbal medicine use among People Living with HIV. The study adopted the phenomenological study design. Data was collected through individual in-depth interviews. Purposive sampling was used to select study participants. Data analysis was done using thematic content analysis. This analysis was done guided by the study objectives to generate emerging themes. Three main themes emerged from the data. The themes framed through the lens of HIV and AIDS care included: (1) patients’ perspectives on ART medication, (2) herbal medicine use in relation to HIV infection and ART adherence, and (3) perceived quality of medical care. Subthemes were discussed under each of the main themes. This study has shown that herbal medicines are widely being used by People Living with HIV and this consequently interrupts their adherence to Antiretroviral Therapy. Some of the People Living with HIV use the herbal medicines separately from ARVs while some use them concomitantly with ARVs. Inadequacies in the health system delivery have also shown to promote use of herbal medicine among People Living with HIV. This has largely affected ART adherence as some of them default ART around the time that they switch to herbal medicine